Brain Antigens Stimulate Proliferation of T Lymphocytes With a Pathogenic Phenotype in Multiple Sclerosis Patients - Gottlieb, Assaf; Pham, Hoai Phuong T.; Lindsey, John William (Frontiers in Immunology, 2022)
A method to stimulate T lymphocytes with a broad range of brain antigens would facilitate identification of the autoantigens for multiple sclerosis and enable definition of the pathogenic mechanisms important for multiple sclerosis. In previous work we found the obvious approach of culturing leukocytes with homogenized brain tissue does not work because the brain homogenate suppresses antigen-specific lymphocyte proliferation. We now report a method that substantially reduces the suppressive activity. We used this non-suppressive brain homogenate to stimulate leukocytes from MS patients and controls. We also stimulated with common viruses for comparison. We measured proliferation, selected the responding CD3+ cells with flow cytometry, and sequenced their transcriptomes for mRNA and T cell receptor (TCR) sequences. The mRNA expression suggested the brain-responding cells from MS patients have a Th17 or T follicular helper phenotype and are potentially pathogenic. The TCR repertoire of the brain-responding cells was clonal with minimal overlap with virus antigens.